The relationship between population and economic growth in asian economies - Wong, Hock Tsen; Fumitaka Furuoka (ISEAS - Yusof Ishak Institute, 2005)
The main aim of the study is to investigate the relationship between population and economic growth in Asian economies. Generally, the results of the Johansen (1988) and Gregory and Hansen (1996) cointegration methods show that there is no long-run relationship between population and economic growth. Nonetheless, the study finds that there is bidirectional Granger causality between population and economic growth for Japan, Korea, and Thailand. For China, Singapore, and the Philippines, population is found to Granger cause economic growth and not vice versa. For Hong Kong and Malaysia, economic growth is found to Granger cause population and not vice versa. For Taiwan and Indonesia, there is no evidence of Granger causality between population and economic growth. On the whole, the relationship between population and economic growth is not straightforward. Population growth could be beneficial or detrimental to economic growth and economic growth could have an impact on population growth.